Concept and Implementation of Religious Character Education for Wiser Use of Technology - Handrianto, Budi; Subagiya, Bahrum; Malik Thoha, Anis (Universitas Darussalam Gontor, 2023)
The unwise utilization of Information and Technology (IT) has resulted in negative impacts within society. This, in turn, gradually contributes to the formation of highly dangerous negative characters that threaten the moral resilience of the nation. The purpose of this paper is to present the concept and implementation of Islamic religious character education as an effort to prevent the negative consequences of the misuse of IT. Through a literature review approach, the authors found that to avoid the adverse effects of unwise IT usage, it is necessary to alter the perspective of learners in line with the Islamic worldview, especially regarding core beliefs in Allah, angels, scriptures, prophets, the Day of Judgment, and predestination. Other essential content that learners should master includes ethical behavior towards Allah, fellow human beings, and oneself. The process of implementing religious character is carried out through ta'dīb and tazkiyatun nafs, involving the stages of takhliyah and taḥliyah. Thus, the objective of this religious character education process is to cultivate learners who are virtuous and wise in their use of IT.